Matematyka

Autorzy:Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Zapisz wyrażenie w jak najprostszej postaci 4.33 gwiazdek na podstawie 6 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a)\ x^3*(x^-5+x^-3+x^-1)=x^(3+(-5))+x^(3+(-3))+x^(3+(-1))=x^-2+x^0+x^2`

 

`b)\ x^-2*(x^6+x^4-x^-2-x^-5)=x^(-2+6)+x^(-2+4)-x^(-2+(-2))-x^(-2+(-5))=x^4+x^2-x^-4-x^-7`

 

`c)\ (x^5-x^-3+x-x^2)*x^6=x^(5+6)-x^(-3+6)+x^(1+6)-x^(2+6)=x^11-x^3+x^7-x^8`

 

`d)\ (x^8+x^6-x^4+x^2)=x^(8-(-3))+x^(6-(-3))-x^(4-(-3))+x^(2-(-3))=`

`\ \ \ =x^(8+3)+x^(6+3)-x^(4+3)+x^(2+3)=x^11+x^9-x^7+x^5`